Myopia and Digit Ratio in Medical College Students - A Gender Based Evidence - Humayun, Shumaila; Hasan, Syed Ali; Aizaz, Haider; Farooq, Tashfeen; Manzoor, Israh; Jameel, Javeria; Siddiqua, Jazla (European Scientific Journal, ESJ, 2018)
Objectives: To measure digit ratios in male and female medical students and compare their relationship with myopia. Study Design: crosssectional study. Place and duration of study: February to September 2016, at Foundation University Medical College. Materials and methodology: Convenient sampling technique was used and 150 students filled a structured questionnaire after giving written informed consent. Students with past history of eye surgery or trauma were excluded. Prescriptions of students were noted for the myopia, and digit lengths measured on a computer via Adobe Photoshop after taking photographs of both hands on scanner and analysed using SPSS version 21. Results: A total of 141 completed questionnaires revealed that 90 students were myopic (63.8 %), of which 39 were males (27.7%) and 51 females (36.2%). Myopic males had larger digit ratios (Right, left and mean) as compared to non-myopic males, whereas myopic females had lower digit ratios as compared to non-myopic females. However a 2 tailed t- test showed significance between right hand digit ratio of male myopes and non-myopes only. Females showed no significance. Pearson’s correlation showed positive correlation of digit ratios and refractive errors in males but negative in females, however it was not significant. Conclusion: Myopia was prevalent in majority of student sample. There were significant differences between the digit ratios of males and females, and right hand digit ratios of males were significantly higher in myopes compared to non myopes. However, Pearson’s correlation was not found significant.